The Impact of Pesantren Environment on MBKM Implementation: ELT Student’ Obstacles - muyasaroh (English Language Teaching Journal, 2025)
This study aims at examining how pesantren environment become obstacles for ELT student in the implementation of MBKM at University of al Qolam Malang. Based on qualitative method employed using interview it is discovered three challenges in terms of obtaining permission to observe Gus at the pesantren, the use of communication technology, specifically social media, which respondent need to use in order to continue communicating with their classmates and lecturers regarding lectures, and time management, as the requirements of MBKM often conflicted with their regular schedule. Key terms: MBKM, Pesantren, ELT